HAPPINESS AND ITS DETERMINANTS: PRELIMINARY FINDINGS AMONG LECTURERS IN AN INDONESIAN UNIVERSITY - Henndy Ginting; Yuni Ros Bangun; Fransisca Budyanto; Anggara Wisesa; Adita Pritasari; Christina Wirawan; Yosi Widarani (Jurnal Sosioteknologi, 2020)
The educational institution is sometimes indicated as a not attractive workplace, which could affect its employee happiness. This research aims to qualitatively identify the state of happiness and its determinants factors including its association with digital technology among lecturers. Digital technology is considered important in the educational area because it helps lecturers to effectively share the information, material, and managing the class. The research was conducted in ITB since it was a university with a technology base. Results indicate a high level of happiness among lectures, especially in pleasant and good life but not meaningful life. There are several determinant factors of happiness identified which are related with interpersonal and intrapersonal. Lectures reported positive and negative impacts of digital technology and happiness. In conclusion, lecturers perceived ITB as their source of happiness especially in providing freedom and opportunity to share knowledge and values.